Health Care Without Harm Europe: Empowering healthcare professionals to drive sustainable change in the sector - Alsius, Mireia Figueras (Journal of the Portuguese Society of Anesthesiology, 2025)
The healthcare sector is one of Europe’s largest industries and has a tremendous environmental, economic, and social footprint.[1] Whereas its mission is to promote health, the sector is a contributor to the ongoing environmental crisis, and it is estimated to be responsible for 4.6% of global carbon emissions.[2] Additionally, chemicals with toxic properties, such as endocrine disruptors, are still widely used, single-use products are common practice, and pharmaceutical residues in water systems are contributing to the rise of antimicrobial resistance (AMR), a growing global health threat. It’s fundamental that the healthcare sector minimises its own environmental impact while working to protect people’s health.